KONTRIBUSI ASESMEN FORMATIF TERHADAP HABITS OF MIND MAHASISWA BIOLOGI - Sriyati, Mrs Siti; Rustaman, Nuryani Y.; Zainul, Mr Asmawi (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2010)
Study about formative assessment contribution to habits of mind of the Biology students purposes to describe weather there is a formative assessment contribution (feedback, self assessment and peer assessment) to the forming of student habits of mind. The research was carried out in Biology Education Departement to students who took Botany Phanerogamae instruction on 2009/2010. Many of formative assessment strategies were applied on theory and practical study, such as group presentation task, concept diagram, to observe practical and presentation activity, drawing book task and practical report. And some of the instrument used on this study were habits of mind tracing questionnaire, work observation sheet on the theoty and practical study, concept diagram, task and rubric for drawing book task, practical report and student questionnaire. The result of the research shows that there is an contribution of formative assessment to the habits of mind, with medium classified with the R value of 0,654. While determination coefficient value is 0.372 which means that 37.2% variation of habits of mind was influenced by formative assessment. Through the path analysis know that the direct influence on feedback, self assessment and peer assessment to habits of mind is 16,7%, 11.1% and 2.6%.Keywords: contribution, formative assessment, habits of mind